Bergamo Field Hospital Confronting COVID-19: Operating Instructions. (19th June 2022) - Spagnolello, Ornella; Rota, Silvia; Francesco Valoti, Oliviero; Cozzini, Claudio; Parrino, Pietro; Portella, Gina; Langer, Martin
Abstract: The coronavirus disease (COVID-19) pandemic represented an unprecedented challenge for health care facilities, and innovative solutions were urgently required to overcome the high volume of critically ill infectious patients, limit in-hospital outbreaks, and limit the risk of occupational infection for health care workers (HCWs). Bergamo was the hardest-hit Italian province by COVID-19, and the local health care system had to undergo a profound and prompt reorganization. A COVID-19-only field hospital was rapidly set up meeting the standards for severe acute respiratory infection (SARI) treatment centers (https://apps.who.int/iris/handle/10665/331603 ). A zones partition, dedicated in-hospital pathways for HCWs, strict infection prevention and control (IPC) measures, and constant staff supervision were key components of our strategy to limit the risk of occupational infection for HCWs. Herein, we present the Bergamo field hospital layout enlightening fundamental IPC measures adopted as a valuable example of a SARI treatment center confronting COVID-19.